White-collar victimisation: A study exploring the harms which employees may incur as a result of working for organisations in which white-collar violations take place - Spalek, Barbara (2000)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University.This project examines two case studies of 'employee victimisation', as part of a wider exploration of 'victimisation' by 'white-collar crime'. Former employees of Robert Maxwell's business empire are interviewed, and the impacts upon their lives of the plundering of their company pension schemes by their boss, Robert Maxwell, are documented. The second case study analysed is that of the closure of the Bank of Credit and Commerce International. Former employees of this bank are interviewed and the impacts upon their lives as a result of working for an institution considered to be corrupt by regulatory authorities are documented. Results reveal that, similar to the consequences of physical and sexual violence and property crime, the individuals taking part in this project endured emotional, psychological, physical, behavioural and financial harms. At the same time, however, unforeseen and undocumented consequences were uncovered which point to the need for further research on 'employee victimisation' and on 'white-collar victimisation' in general.This work is funded by the Law Department at Brunel University